2022
DOI: 10.1002/jee.20465
|View full text |Cite
|
Sign up to set email alerts
|

Engineering graduate students’ mental health: A scoping literature review

Abstract: Background: Mental health issues reported among college-aged individuals have increased. Prevalence of these issues has an established impact on students' personal, professional, and academic outcomes. Graduate students experience unique stressors that impact their mental health. In particular, engineering graduate students have lower help-seeking tendencies, which can impact the severity and length of their mental health problems. Purpose: We investigate the literature concerning engineering graduate students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 115 publications
(239 reference statements)
0
14
0
Order By: Relevance
“…Three percent have chronic illness. Paralleling the rising concern over mental health issues in higher education (Bork & Mondisa, 2022; Dolmage, 2017), 1 in 11 students (9%) experience mental health difficulties. This is generally consistent with national‐level data that finds that 19% of college students in the United States have some form of disability (Jensen & Cross, 2021; McCall et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three percent have chronic illness. Paralleling the rising concern over mental health issues in higher education (Bork & Mondisa, 2022; Dolmage, 2017), 1 in 11 students (9%) experience mental health difficulties. This is generally consistent with national‐level data that finds that 19% of college students in the United States have some form of disability (Jensen & Cross, 2021; McCall et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Although not available in these data, a growing literature in engineering education addresses the experiences of people with learning disabilities and forms of neurodiversity (i.e., diverse ways of thinking, communicating, and behaving) such as ADHD and autism and has begun to recommend pedagogical shifts that can provide expanded accessibility along these dimensions (Asghar et al, 2017; Chrysochoou et al, 2021; Syharat et al, 2020). Attention to physical disabilities and chronic and mental illness in engineering has lagged in comparison (Bork & Mondisa, 2022; Jensen & Cross, 2021; Spingola, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This study is also among the first to highlight the impacts of graduate school on graduate student well‐being and mental health in engineering as an explicit cost of persistence, from the lens of EVT. Though literature indicates there is a mental health epidemic at the graduate level (Evans et al, 2018; Levecque et al, 2017), graduate student well‐being and mental health are underexplored in engineering education literature (Bork & Mondisa, 2022). Past work has demonstrated that engineering graduate students expect to be “stressed and depressed” in graduate school (Zerbe et al, 2020), but our participants noted how the costs to their diminished well‐being affect their considerations of attrition.…”
Section: Discussion and Opportunities For Future Scholarshipmentioning
confidence: 99%
“…In marketing, it could enable personalized advertising based on consumers' emotional responses. However, ethical considerations regarding privacy, consent, and manipulation must be carefully addressed as emotional computing technology continues to evolve and integrate into our daily lives [4].…”
Section: Introductionmentioning
confidence: 99%